Kidney Disease Among Registered Métis Citizens of Ontario: A Population-Based Cohort Study. Issue 1 (11th April 2017) - Hayward, Jade S.; McArthur, Eric; Nash, Danielle M.; Sontrop, Jessica M.; Russell, Storm J.; Khan, Saba; Walker, Jennifer D.; Nesrallah, Gihad E.; Sood, Manish M.; Garg, Amit X.
Background: Indigenous peoples in Canada have higher rates of kidney disease than non-Indigenous Canadians. However, little is known about the risk of kidney disease specifically in the Métis population in Canada. Objective: To compare the prevalence of chronic kidney disease and incidence of acute kidney injury and end-stage kidney disease among registered Métis citizens in Ontario and a matched sample from the general Ontario population. Design: Population-based, retrospective cohort study using data from the Métis Nation of Ontario's Citizenship Registry and administrative databases. Setting: Ontario, Canada; 2003-2013. Patients: Ontario residents ≥18 years. Measurements: Prevalence of chronic kidney disease and incidence of acute kidney injury and end-stage kidney disease. Secondary outcomes among patients hospitalized with acute kidney injury included non-recovery of kidney function and mortality within 1 year of discharge. Methods: Database codes and laboratory values were used to determine study outcomes. Métis citizens were matched (1:4) to Ontario residents on age, sex, and area of residence. The analysis included 12 229 registered Métis citizens and 48 916 adults from the general population. Results: We found the prevalence of chronic kidney disease was slightly higher among Métis citizens compared with the general population (3.1% vs 2.6%, P = 0.002). The incidence of acute kidney injury was 1.2 per 1000 person-years in both Métis citizens and the general population ( P = 0.54). Of those hospitalized with acute kidney injury, outcomes were similar among Métis citizens and the general population except 1-year mortality, which was higher for Métis citizens (24.5% vs 15.3%, P = 0.03). The incidence of end-stage kidney disease did not differ between groups (<3.0 per 10 000 person-years, P = 0.73). Limitations: The Métis Nation of Ontario Citizenship Registry only captures about 20% of Métis people in Ontario. Administrative health care codes used to identify kidney disease are highly specific but have low sensitivity. Conclusions: Rates of kidney disease were similar or slightly higher for Métis citizens in Ontario compared with the matched general population.